Free radical scavenging effect of extracts from \(Isaria cicadae\) F0004 in Vietnam - Lam, Khac Ky; Huynh, Thi Nguyet; Dinh, Minh Hiep; Ngo, Hung Dai (Academia Journal of Biology, 2023)
Isaria cicadae, currently identified as Paecilomyces cicadae (Miq.) Samson (Cordycipitaceae, Hypocreales, Ascomycetes), is a parasitic fungus on cicadas and is considered a folk medicine in traditional medicine. In this research, the antioxidant activity of some extracts from the biomass and fruit bodies of Isaria cicadae F0004 isolated in Vietnam was investigated. The results showed that the Ethyl acetate (EA) fraction extract of the biomass of Isaria cicadae F0004 exhibited the best antioxidant activity in vitro, with IC50 values of 159.73 ± 7.33 μg/mL (DPPH assay) and 379.25 ± 7.33 μg/mL (ABTS assay). Meanwhile, the EA fraction extract of the fruit bodies of I. cicadae F0004 showed antioxidant activity with IC50 values of 90.8 ± 2.36 μg/mL (xanthine oxidase inhibition), 68.631 ± 0.632 μg/mL (protein membrane protection), 19.042 ± 1.072 μg/mL (lipid membrane protection). Furthermore, the EA fraction extract of the fruit bodies of I. cicadae F0004 exhibited a strong capability for DNA damage protection at 100 μg/mL concentration and ∆OD4000 μg/mL = 0.422 ± 0.014 (reducing power). Therefore, the EA fraction extract of I. cicadae F0004 serves as an effective free radical scavenger and a potential source of natural antioxidants, and this study contributes more information on the biological activities of I. cicadae F0004 from local raw materials.